A 15‐year analysis of precipitation and rain garden response. Issue 11 (8th November 2022) - Amur, Achira; Wadzuk, Bridget; Traver, Robert
Abstract: The longevity and resilience of green stormwater infrastructure (GSI) over time is a key concern as municipalities around the world move to incorporating GSI into stormwater management strategies. The Villanova University bioinfiltration rain garden (BRG) was constructed as a retrofit of an existing parking lot traffic island in 2001 and has been monitored since 2003, providing a long hydrological data record that is valuable for an in‐depth analysis of rainfall characteristics and rain garden response. The goal of this research is to use the data to assess the reliability of a rain garden's response in terms of its ability to manage incoming runoff from different rainfall event sizes, distributions, and antecedent conditions. A high‐resolution analysis of rainfall event frequency was done for all rainfall events within a 15 year (2003–2018) study period. Rainfall events were discretized into 2.5 mm, 2‐hour bins. Rainfall within each bin were compared and contrasted to discern the similarity of the rainfall distribution and trends in rain garden response. The rainfall‐runoff parameters were also analysed to understand if the occurrence of overflow could be expected based on storm characteristics. Results show that of the 1202 recorded events, 82% of them were less than 25 mm. Approximately 15% of all observed events resulted in measurable overflow, ranging from 0.01 to 685 m 3 . When compared to the design storm standards set for the region for GSI (the 2‐year, 24‐hour event), only 1% of all the storms recorded at the site were higher in terms of precipitation amount and event duration. In terms of design, the static rainfall volumes set by the standards did not represent the variety of storms experienced at the site. The overall analysis provided lessons into system components that can be used to advance green infrastructure design and policy standards. Abstract : The performance of a rain garden is studied using 1202 events recorded over a period of 15 years (2003–2018). The distribution of events experienced by the system is assessed in relation to the design regulations set for the region. The rain garden's response to characteristically similar storms is analysed in terms of the rainfall‐runoff parameters with overflow as a metric of performance.